Implementation Of Law Number 8 Of 2016 Concerning Persons With Disabilities In The Protection And Fulfillment Of The Rights Of Persons With Social Disabilities In Barru Regency - Sukmiah, Sukmiah; Masyitah, Masyitah (Jurnal Info Sains : Informatika dan Sains, 2024)
This study aims to find out the implementation of Law Number 8 of 2016 concerning persons with disabilities in the protection and fulfillment of the rights of persons with disabilities and the factors that hinder Law Number 8 of 2016 concerning persons with disabilities in the protection and fulfillment of the rights of persons with disabilities in the Barru Regency Social Service by using the type of qualitative research the type of data used consists of primary and secondary data, accompanied by data collection techniques, namely, observation, interviews and documentation. Meanwhile, the analysis techniques used are, through the stages of data collection, data reduction, data presentation and conclusion drawn. The results of this study show that the implementation of Law Number 8 of 2016 concerning persons with disabilities in the protection and fulfillment of the rights of persons with disabilities in the Barru Regency Social Service is quite good with indicators, namely the implementation of Law Number 8 of 2016, problems encountered by persons with disabilities in accessibility, the existence of regional regulations (PERDA) on the fulfillment of the rights and protection of persons with disabilities, rights obtained by persons with disabilities, duties and functions of the government for persons with disabilities, while the factors that affect the implementation of Law Number 8 of 2016 concerning persons with disabilities in the protection and fulfillment of the rights of persons with disabilities in the Barru Regency Social Service are factors of legal structure or legal substance that still lack technical performances that specifically regulate persons with disabilities and organized infrastructure facilities as well as the capacity of the apparatus The government still lacks understanding of the main duties, functions and socializing on disabilities.